Clinical Diagnosis of Hypersensitivity Pneumonitis - Lacasse, Yves; Selman, Moises; Costabel, Ulrich; Dalphin, Jean-Charles; Ando, Masayuki; Morell, Ferran; Erkinjuntti-Pekkanen, Riitta; Muller, Nestor; Colby, Thomas V; Schuyler, Mark; Cormier, Yvon (American journal of respiratory and critical care medicine, 2003)
The diagnosis of hypersensitivity pneumonitis (HP) is difficult and often relies on histopathology. Our objective was to identify diagnostic criteria and to develop a clinical prediction rule for this disease. Consecutive patients presenting a condition for which HP was considered in the differential diagnosis underwent a program of simple standardized diagnostic procedures. High-resolution computed tomography scan and bronchoalveolar lavage (BAL) defined the presence or absence of HP. Patients underwent surgical lung biopsy when the computed tomography scan, BAL, and other diagnostic procedures failed to yield a diagnosis. A cohort of 400 patients (116 with HP, 284 control subjects) provided data for the rule derivation. Six significant predictors of HP were identified: (1) exposure to a known offending antigen, (2) positive precipitating antibodies to the offending antigen, (3) recurrent episodes of symptoms, (4) inspiratory crackles on physical examination, (5) symptoms occurring 4 to 8 hours after exposure, (6) and weight loss. The area under the receiver operating characteristic curve was 0.93 (95% confidence interval: 0.90-0.95). The rule retained its accuracy when validated in a separate cohort of 261 patients. The diagnosis of HP can often be made or rejected with confidence, especially in areas of high or low prevalence, respectively, without BAL or biopsy.